Prevalence and determinants of smoke-free homes in 12 European countries: the TackSHS Survey - Olena Tigova; Chiara Stival; Yolanda Castellano; Alessandra Lugo; Marcela Fu; Anna Mar López; Cristina Martínez; Joan B. Soriano; Rachel O'Donnell; Sean Semple; Maria J. López; Esteve Fernández; et al. (ERJ Open Research)
Background Homes are one of the primary locations where people are exposed to second-hand smoke (SHS) in Europe. We describe the prevalence and identify the main determinants of having home-smoking restrictions in 12 European countries. Methods Cross-sectional survey in 12 European countries conducted in 2017–2018 (TackSHS project). Approximately 1000 participants representing the general population aged ≥15 years of each country were interviewed face to face. Individual- and country-level characteristics were explored through adjusted prevalence ratios (PRs) obtained from multilevel Poisson models with random effects. Results Among 11 734 participants, 70.2% (95% confidence interval (CI) 69.4–71.0%) had smoke-free homes and 17.5% (95% CI 16.8–18.2%) had partial home-smoking restrictions in place. Prevalence of smoke-free homes ranged from 44.4% in Greece to 84.5% in England. Having a smoke-free home was significantly inversely associated with current (PR=0.60) or former (PR=0.95) smoking and living in a household with one (PR=0.70) or two or more (PR=0.58) people who smoke. It was also significantly associated with being ≥65 years old (PR=1.05), being female (PR=1.07), having a high educational level (PR=1.09) and living with children (PR=1.09). Having a smoke-free home was associated with living in northern Europe, while partial home-smoking restrictions were more likely among respondents from eastern Europe and countries with lower per capita gross domestic product. Conclusions The prevalence of smoke-free homes in Europe is relatively high, but with large variability across countries. European countries with a lower prevalence of smoke-free homes should implement tailored interventions targeting identified determinants and incorporate the success of other countries.